About the ways of biological participation of iodine in maintenance of homoeostasis and determination of iodine deficiency in an organism - Мukasheva, G.Zh.; Zernke, B.; Мukasheva, М.А (KSU Pub, 2016)
Deficiency of iodine in environment is the long-term factor which doesn’t change throughout centuries of human existence. Certainly, in iodic security of an organism food plays large role, by means of which geochemical features of the territory and social conditions are realized. Results of numerous researching work by iodic security of an organism testify that in the conditions of lack of iodic prevention, iodine deficiency conditions of the population have mass character. By carrying out hygienic researches on Kazakhstan, practically in all regions, in a varying degree, iodic insufficiency was revealed.
Гомеостазды бір қалыпта ұстауға жəне ағзадағы йодтапшылықты анықтауға йодтың қатысының биологиялық жолдары жайлы
О путях биологического участия йода в поддержании гомеостаза и определения йододефицита в организме
Keywords: thyroxine; diiodotyrosine; triiodothyronine; oxidizing processes; toxic hyperfunction; pathological processes